Influence of Operating Cost, Production Cost and Sales Volume on Net Profit of IDX-Listed Pharmaceuticals - Shintya Putri Salsabila; Ana Kadarningsih (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study analyzes the effect of operating costs, production costs, and sales volume on net profit in pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2024. Using a quantitative method with panel data regression analysis, this study took a sample of 11 companies and secondary data from financial reports. The results of the hypothesis test show that operating costs, production costs, and sales volume partially have a positive and significant effect on net profit. These findings are consistent with existing literature and indicate that efficient cost management and increased sales volume are crucial factors in maximizing profitability in the pharmaceutical sector. Furthermore, this research is also relevant to Agency Theory, which suggests that management, as agents, must manage costs and sales transparently to align their interests with those of shareholders, ultimately leading to the sustainable increase of company value. This study contributes to understanding key factors driving financial performance in the industry.